Deteksi Salmonella spp. pada Telur Ayam Konsumsi dari Peternakan Ayam Ras dan Pasar Tradisional di Bali - Yansri, Alifianita Anake; Plumeriastuti, Hani; Effendi, Mustofa Helmi (Jurnal Veteriner; Vol 22 No 1 (2021)DO - 10.19087/jveteriner.2021.22.1.93, 2021)
This study aims to early detect Salmonella spp. and identify serotypes in commercial chicken eggs from layer chicken farms and traditional markets in Bali. Early detection study of Salmonella spp. was carried out by conventional bacteriological methods, while serotype identification by duplex Polymerase Chain Reaction (d-PCR) test against the invA gene from Salmonella spp. and the sefA gene from Salmonella enteritidis. Egg samples in this study were taken from 10 layer chicken farms in Bali which included districts of Bangli, Gianyar, Tabanan and Karangasem. Egg samples from traditional markets were taken from 18 traditional markets from the districts of Bangli, Gianyar, Tabanan, Karangasem, Badung, and Denpasar City. Samples were eggshells and egg whites. Analysis of positive results from Salmonella spp. described descriptively. The results showed that eggshells and white eggs from all of the layer chicken farms are negative contaminated with Salmonella spp. (0%). In eggshell samples taken from the traditional markets of Taman Bali and Tulikup from the districts of Bangli and Gianyar, positive with Salmonella spp. (11,1%) by conventional bacteriological tests. In the duplex Polymerase Chain Reaction test, S. enteritidis serotypes were identified. The finding contamination of Salmonella enteritidis in commercial chicken eggs from traditional markets require periodically detection to prevent the occurrence of salmonellosis due to consumption of contaminated chicken eggs in traditional markets in Bali.